MORAL MESSAGE ON THE VIDEO JOURNALIST CLIP “YURA YUNITA- TUTUR BATIN”: (Charles Sanders Peirce Semiotics Analysis) - Fahri Fidali Purba; M.Yose Rizal Saragih (KABILAH : Journal of Social Community, 2022)
Abstract: This research discusses the moral message contained the video clip Yura Yunita entitled Tutur Batin. This research focuses on knowing what are the moral messages contained in the video clip “Yura Yunita- Tutur batin". The research was to find out what the moral message conveyed in the video clip, researcher conduct qualitative methods and data obtained and then analyzed by Charles Sanders Peirce's semiotic approach to determine the symbolic meaning of the moral message to be conveyed in the video clip. The results showed that in the video clip “Yura Yunita-Tutur batin " those are many moral messages that we can take lessons for ourselves, among others, in the first scene women must be brave and strong, in the second scene shows that do not feel discouraged and insecure, the fourth scene shows the moral message do not look at someone from the physical, and scene 5 to 7 there is a moral message that is not perfect is not a problem because every human being has their own uniqueness. Keywords: Moral Message, Semiotics, Video clip